Receptivity to research in policing: Results from a survey of Canadian police professionals - Khanizadeh, Ariane-Jade (International journal of police science & management, 2023)
Previous surveys have demonstrated that not all police professionals are open to the idea that research can play an important role in policing. To examine how Canadian police professionals view this issue, we conducted a survey of 598 civilian and sworn police professionals from seven Canadian police services. The survey responses allowed us to gauge receptivity towards research and determine what factors predict receptivity. We also examined factors that differentiate the most receptive police professionals from others. Compared with previous surveys, our respondents were more receptive to research. Furthermore, having higher education, holding a more senior rank, and being exposed to research (e.g., attending conferences) were associated with higher levels of receptivity to research. The results from this study can potentially be used to increase receptivity to research among police professionals, which may help police services become more efficient and effective.